2016
DOI: 10.1016/j.jocm.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling choice when price is a cue for quality: a case study with Chinese consumers

Abstract: Experience products are those the quality of which cannot be ascertained until after consumption, forcing consumers to base their purchase decision on an expectation of the product's quality. This expected quality is based on cues available before purchase, among which price is noteworthy, as consumers tend to believe that higher prices imply higher quality. But price also stresses the consumers' budget restriction, inducing a double-and conflicting-global effect on purchase probability. Using the traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 58 publications
1
20
0
3
Order By: Relevance
“…The means-end model shows that price influences perceived monetary price; perceived monetary price influences perceived sacrifice and perceived quality. Then perceived sacrifice and perceived quality influence perceived value, which in turn influences purchase intentions.Researchers have applied the price-quality-value model (Monroe and Krishnan 1985) and the means-end chain model (Zeithaml 1988) to explain the effect of price on customers' perceptions and confirmed the relationships proposed in these models (Dodds et al 1991;Palma et al 2016;Rao and Monroe 1989;Suri and Monroe 2003). These studies have consistently shown that there is a positive effect of price on consumers' perceptions of quality.…”
mentioning
confidence: 80%
“…The means-end model shows that price influences perceived monetary price; perceived monetary price influences perceived sacrifice and perceived quality. Then perceived sacrifice and perceived quality influence perceived value, which in turn influences purchase intentions.Researchers have applied the price-quality-value model (Monroe and Krishnan 1985) and the means-end chain model (Zeithaml 1988) to explain the effect of price on customers' perceptions and confirmed the relationships proposed in these models (Dodds et al 1991;Palma et al 2016;Rao and Monroe 1989;Suri and Monroe 2003). These studies have consistently shown that there is a positive effect of price on consumers' perceptions of quality.…”
mentioning
confidence: 80%
“…In the case of wine, it has even been observed at a neurological level (Plassmann et al ). A way to deal with this issue was presented by Palma et al ().…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, hybrid choice models provide the ability to disentangle the causation, mediation, and moderation effects typical of structural equation modelling while having a more accurate dependent variable than a rating-based willingness to purchase. To date the only example of hybrid choice models applied to wine consumer research is the work of Palma et al (2016).…”
Section: Discrete Choice Experiments (Dces)mentioning
confidence: 99%